Establishing an anaesthetist-delivered propofol sedation service for advanced endoscopic procedures: implementing the RCA/BSG guidelines. Issue 3 (2nd November 2017) - Smith, Ian; Durkin, Damien; Lau, Kaw Wai; Hebbar, Srisha
Abstract : Background: Following recommendations from the Royal College of Anaesthetists and the British Society of Gastroenterology, we report our results of propofol sedation for complex endoscopic procedures delivered by a single consultant anaesthetist over a 5-year period. Methods: A weekly session was provided in the endoscopy department for procedures that were complex or could previously not be completed successfully. Deep sedation was provided by intermittent propofol bolus doses, supplemented with fentanyl where necessary, titrated to clinical effect. Patients were usually in semiprone or lateral positions and spontaneously breathed air supplemented with nasal oxygen. Service evaluation included patient recall, endoscopist satisfaction with conditions, procedural success and airway-related adverse outcomes. Results: We completed 1000 procedures, 42.5% of which were endoscopic retrograde cholangiopancreatography, with the remainder comprising a diverse range of endoscopic procedures of 3–156 min duration. Procedural conditions were excellent in 79% of cases, 261 procedures were completed which had been previously abandoned, 246 patients (24.6%) had a better experience than previously and none recalled any part of their procedure. Three patients required transient bag and mask ventilation, and nasal airways were used in 12 patients, but none required tracheal intubation or vasopressor support. Conclusions: These guidelines facilitated a propofol sedation service with considerable benefits for patients and endoscopists. Provision of deep propofol sedation by an anaesthetist, in patients with an unsecured airway, appears practical, effective and efficient. Small adjustments to the airway were fairly common, but the incidence of adverse events and requirement for airway instrumentation was low.